Chapter 25: Digital campaigning: how digital media change the work of parties and campaign organizations and impact elections - Jungherr, Andreas (Edward Elgar Publishing, 2023)
Digital media have become important elements of political parties and campaign organizations all over the world. Examples from U.S. presidential campaigns dominate the public imagination of digital campaigning. At the same time, it is important to recognize that the uses of digital media in politics vary considerably depending on campaign contexts and resources. This makes necessary the analysis of the use of digital media by parties and campaign organizations in varying temporal and international contexts instead of expecting the examples from the U.S. to apply globally. The chapter will proceed by a discussion of some of the dominant theoretical and empirical approaches to the study of digital campaigning. Following this, the chapter will use a framework focused on campaign functions for the discussion of digital campaigning: The impact of digital media on organizational structures and work routines, resource collection and allocation, achieving presence in communication spaces and reach to audiences of interest, and the use of digital media as a symbol for professionalism and innovation of parties and their candidates.